Moving out of the bottom of the economy? Constraints to firm transition in the Indian informal manufacturing sector - Rajesh SN Raj; Kunal Sen (IZA Journal of Labor & Development, 2016)
The predominant type of firms in developing countries is small family firms and the self-employed in the informal sector. Very few family firms make the transition to larger firms employing non-family labour. In this paper, we examine the reasons for the low presence of firms employing non-family labour in the informal sector, using a firm-level data set drawn from nationally representative repeated cross-sectional surveys of the Indian informal manufacturing sector. We find that the key constraint to firm transition is firm capabilities, followed by the level of urbanisation, access to electricity and roads, and human capital, with financial constraints playing a lesser role.
Keywords: O17; L25; D22; 330; Informal sector; Firm transition; Firm growth; India